Lid splinting eyelid retraction technique: a minimised sterile approach for intravitreal injections. Issue 9 (15th December 2017) - Munro, Monique; Williams, Geoff R; Ells, Anna; Fielden, Michael; Kherani, Amin; Mitchell, Patrick; Ruzicki, Jessica; Adatia, Feisal A
Abstract : Background/aims: To describe an alternative technique for avoiding contact with the lids and lashes, without the use of a lid speculum, during intravitreal anti-vascular endothelial growth factor injections. Methods: Retrospective case series of all patients undergoing intravitreal injections of bevacizumab and ranibizumab, with the lid splinting retraction technique from January 2010 to December 2015. Injections performed by six vitreoretinal specialists were included. The key preinjection ocular surface preparation includes topical anaesthetic, 5% povidone-iodine and a subconjunctival injection of 2% lidocaine with epinephrine. A second instillation of 5% povidone-iodine is given and the intravitreal injection is then performed. No lid speculum is used. A search of the electronic medical records identified patients diagnosed with postinjection endophthalmitis and charts were reviewed to ensure inclusion criteria were met. The main outcome measure was incidence of postinjection endophthalmitis. Results: A total of 78 009 consecutive intravitreal injections were performed, of which 22 207 were bevacizumab and 55 802 were ranibizumab. In this cohort of patients (n=6320), 12 cases of endophthalmitis developed, corresponding to a rate of 0.015%. Conclusions: The technique of eyelid retraction for intravitreal injection has a low rate of endophthalmitis, similar to the reported rates using a metal lid speculum. This is beneficial for both the physician and the patient as it minimises patient discomfort as well as the duration of the procedure. To our knowledge, this is one of the largest studies performed to date evaluating intravitreal injection-related endophthalmitis.